(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
To solve the environmental problems caused by the algae, pyrolysis experiment was studied to produce bio-oil with the wild cyanophyta from Chaohu lake for the first time. The results showed that the suitable temperature, carrier gas flow rate, and the smaller particle size were better for liquid products generation, the liquid (bio-oil) yield obtained maximum (66 %) at temperature of 450 oC, carried gas flow rate of 50 mL/min and particle size of less than 0.25 mm. The main ingredients of liquid product from cyanophyta pyrolysis consisted of hydrocarbons, nitrogenous compounds, acids and other organic compounds (such as alcohols, phenols esters and non-identified materials). Acid content was the highest and greatly affected by temperature. The content of hydrocarbons was about 15%.